Improved Hemodynamic Status of Head Injured Patients in the Emergency Unit (ER): Literature Review - Hamdani, Dadi; Husain, Fida (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2021)
Background: Head injury is a serious problem that can lead to death and even death. Handling of head injuries starts from protecting the brain with blood flow to the brain so that hypoxia or brain ischemia does not occur. Hemodynamics is the result of measuring systolic and diastolic blood pressure, pulse rate, and respiratory rate. Objectives: This literature review aims to find out what interventions can be done when there is an increase in hemodynamic status in head injury patients Methods: This database search was conducted by searching on google scholars with the keywords head injury, hemodynamics. The inclusion criteria of this literature review are articles that were researched within the last 5 years with the year published 2015-2020, full text, using the Indonesian language, the article that used is the article. Results: Interventions that can be done when there is an increase in hemodynamic status in head injury patients are giving oxygen and increasing 30o, giving oxygen through a simple mask and head position 30o, giving head-up position 30o compared to 15o position, giving nasal prong oxygenation therapy and murotal therapy Al-Qur'an for 30 minutes 3 times/day. Conclusion: All interventions resulting from this literature review were in the form of giving oxygen and increasing the head 30o, giving oxygen through a simple mask and head position 30o, giving the head position 30o compared to 15o position, giving nasal branch oxygenation therapy, and murotal Al-Qur'an therapy for 30 minutes 3 times/day.